Clinical trial management: a profession in crisis? - Mitchell, E. J.; Goodman, K.; Wakefield, N.; Cochran, C.; Cockayne, S.; Connolly, S.; Desai, R.; Hartley, S.; Lawton, S. A.; Oatey, K.; Rhodes, S.; Savage, J. S.; et al. (Current controlled trials in cardiovascular medicine, 2022)
Clinical trial managers play a vital role in the design and conduct of clinical trials in the UK. There is a current recruitment and retention crisis for this specialist role due to a complex set of factors, most likely to have come to a head due to the COVID-19 pandemic. Academic clinical trial units and departments are struggling to recruit trial managers to vacant positions, and multiple influences are affecting the retention of this highly skilled workforce. Without tackling this issue, we face major challenges in the delivery on the Department of Health and Social Care’s Future of UK Clinical Research Delivery implementation plan. This article, led by a leading network of and for UK Trial Managers, presents some of the issues and ways in which national stakeholders may be able to address this.